PEMANFAATAN IKAN UNTUK INISIASI USAHA MAKANAN PADA ANAK-ANAK YAYASAN PANTI ASUHAN BUMI NUSANTARA KOTA BENGKULU - Nyayu Neti Arianti; Melli Suryanti (Universitas Bengkulu, 2018)
This activities aimed to: 1) to apply knowledge and skills about processing fish into a variety of food (pempek, fish nugget and fish balls) to girls in the orphanage, and 2) to evaluate those knowledge and skills from production, economic and prospective aspect. Activity method included counseling to transfer knowledge about how to process fish into healthy food worth selling is Learning by Doing method so that science and skill more easily understood. Evaluation of known science and skill was done by descriptive method. This activites were very interesting for participants because the science and skills that were shared easily implemented. All participants were enthusiastic. The 23 participants were divided into three groups. The first group maked pempek, the second group maked fish nuggets and the third group maked fish balls. The evaluation of the initiation activities of this fish processing business indicated that the knowledge and skill that was applied, ie from the aspect of production (easy to do) was expressed by 94.4% of participants, from economic aspect (feasible and profitable) was expressed by 100% participants, and from the aspect of prospective (the initiation of this effort aspired to be realized into a home business) was expressed by 100% of participants. Keywords: fish processing, food, business initiation, orphanage